Minecraft : construction handbook - Needler, Matthew; Southam, Phil; Barker, James; Cordner, Theo (New York : Scholastic, 2014)
An official guide to Minecraft construction shares essential tips and tricks for building creative structures and innovations ranging from theme parks and waterslides to pirate coves and animal cannons.
"An official Mojang book"--Cover.
Includes bibliographical references (page [79]).
1050
Keywords: Minecraft (Game) -- Handbooks, manuals, etc. -- Juvenile literature; Video games -- Handbooks, manuals, etc. -- Juvenile literature; Minecraft (Game) -- Handbooks, manuals, etc; Video games -- Handbooks, manuals, etc